Saham Syariah: Tantangan dan Peluang Investasi Berbasis Prinsip Keuangan Islami.pdf - Hadistiara, Aulia; Andini; Amanda, Nurulia (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2023)
The development of the sharia financial sector is currently in a good position, especially for Indonesia's population, which is predominantly Muslim, of course this is a good condition for the development of sharia finance to be even more advanced. However, in the development of sharia finance, there are not only opportunities for progress, but there are also challenges that accompany it. This research method uses literature review sourced from Google Scholar, Research Gap and websites. Challenges in sharia stock investment include in-depth analysis required and lack of awareness and monitoring and compliance issues. Opportunities in Sharia Stock Investment, including Sharia-Based Economic Growth, Stock Endowments and Diversification and periodic evaluations ensure that shares continue to comply with sharia principles. Developments in Sharia Shares, including a Solid Rising Trend, Increased Liquidity and Share Value, and Driving Innovation and Diversification.